Desde fuera y desde dentro: aproximación preliminar a los estudios sobre identidad cultural en afrocolombianos - Díaz Rico, María Elena (Universidad de San Buenaventura - Cali, 2017)
This literature review focuses on writings about the African descent population, in which we find two dominant types of looks: an external and an internal one. We found that most approaches focus on the analysis and criticism to the results obtained based on the external look. Thus, it is evident the need for increasingly favoring the internal look as well as the feelings of a group, in order to understand their behavior in a complex social system and perhaps find clues to the preservation of life and a peaceful ethnic coexistence.